POLA PERUBAHAN KEBIJAKAN LUAR NEGERI CINA - Andy Hallang Lewa (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2007)
Although most of the time China is embedded with its tight principles, its international affair’s policies always changing as they never hesitate to change their foreign affair policy to pursue its ultimate goal. China’s foreign affair policies are influenced by international and national condition as well as their ideology and romantics of the past glory. Keywords: Foreign affair politics, traditional china, modern china, Mao Zedong world, two sides, in between zone, three worlds, Deng Xiaoping world